Identifying Errors and Fraud in Regional Financial Management: A Literature Review - Mia Aulia Putri Camsana; Dhea Anggia; Siti Nabila; Mariana Mariana (CV. Kalimasada Group, 2024)
This research aims to identify forms of errors and fraud that occur in regional financial management and analyze the impact on accountability and transparency. This research uses the systematic literature review (SLR) method to select relevant literature which includes scientific journals, books, articles and other academic documents. The data collection process is carried out through databases such as Google Scholar and ResearchGate. This research focuses on financial management errors, such as calculation errors, delays in proof of transactions, and non-compliance with accounting standards which often occur due to weak internal controls. In addition, fraud that occurs in the form of misuse of funds and manipulation of financial reports is influenced by factors such as pressure, opportunity and rationalization. The impact of errors and fraud is very broad, not only causing financial losses, but also reducing the quality of public services, worsening public trust, and disrupting the sustainability of regional development. This research suggests the importance of improving the supervision system, increasing transparency, and optimizing regional financial management to prevent errors and fraud. Thus, this research provides insight into improving regional financial governance in order to achieve community welfare.